Leptin ameliorates ischemic necrosis of the femoral head in rats with obesity induced by a high-fat diet - Zhou, Lu (Sci Rep, 2015)
Obesity is a risk factor for ischemic necrosis of the femoral head (INFH). The purpose of this study was to determine if leptin treatment of INFH stimulates new bone formation to preserve femoral head shape in rats with diet-induced obesity. Rats were fed a high-fat diet (HFD) or normal chow diet (NCD) for 16 weeks to induce progressive development of obesity. Avascular necrosis of the femoral head (AVN) was surgically induced. Adenovirus-mediated introduction of the leptin gene was by intravenous injection 2 days before surgery-induced AVN. At 6 weeks post-surgery, radiologic and histomorphometric assessments were performed. Leptin signaling in tissues was examined by Western blot. Osteogenic markers were analyzed by real-time RT-PCR. Radiographs showed better preservation of femoral head architecture in the HFD-AVN-Leptin group than the HFD-AVN and HFD-AVN-LacZ groups. Histology and immunohistochemistry revealed the HFD-AVN-Leptin group had significantly increased osteoblastic proliferation and vascularity in infarcted femoral heads compared with the HFD-AVN and HFD-AVN-LacZ groups. Intravenous injection of leptin enhanced serum VEGF levels and activated HIF-1α pathways. Runx 2 and its target genes were significantly upregulated in the HFD-AVN-Leptin group. These results indicate that leptin resistance is important in INFH pathogenesis. Leptin therapy could be a new strategy for INFH.